Comparison among Four Method for Diagnosing Rubella Virus in Pregnant Women (Medico Legal Update, 2021)
This study was intended to determine rubella virus seroprevalence in pregnant women. The samples included240 women who attended during the duration from October 2018 to May 2020 Al-Batool GynecologyHospital in Baqubah District. Women’s age ranged from 16-45 years; their age mean was 26.38 years. Dataincluding age, number of previous abortions. Sera were collected from each woman, and the levels of rubellaIgG and IgM were detected by use Electrochemiluminescence (ECLIA), enzyme-linked immunosorbentassay (ELISA) and On Site Rubella IgG/IgM Rapid (OnSite) tests. Also, RT-PCR test are used to detectrubella viral RNA. The results revealed that anti-rubella IgG antibodies for the 240 pregnant women wereranges from 84.58 % to 89.58 % depending on the method tested used. While the anti-rubella IgM antibodiesfor the 240 pregnant women were ranges from 5 % to 5.41 % depending on the method tested used. Only 8from 240 specimens of pregnant women are rubella viral RNA positive with (3.33 %) percentage by RT-PCRtest. In relation to the history of abortion, the seropositivity of rubella antibodies were (61.42 %) of pregnantwomen had history of abortion with significant relation P< 0.05, however the abortion frequency amongPregnant patients have the past of one or more abortions with the nonsignificant P>0.05 relation.